The Eurozone's arrested adolescence: Sketching a way out of the crisis - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2012)
The Eurozone crisis has been reinforced and prolonged by leaders' inability to agree on robust and credible crisis responses. Individual governments are experiencing sovereign deficit and debt crises, but not the Eurozone at large. Its fiscal position is manageable. The Eurozone is rather going through a crisis of the sovereign - or a crisis of government. Too many of the crisis solutions offered by Eurozone leaders have commanded neither authority nor electoral legitimacy. (...)
Keywords: 330; Wirtschaftskrise; Schuldenkrise; Haushaltsdefizit; Eurozone